Oil policy and investment licenses contracts in Iraq (analytical study) - Mayah Shabib Al Shammari; Ahmed Sajjad (مجلة الغري للعلوم الاقتصادية والادارية)
As it is known, oil is one of the most important economic resources in Iraq, therefore the oil policy is the cornerstone for the investment of this vital resource, where it contributes to the revenues of the Iraqi budget were more than 90%. Since the discovery of Baba Gharghar field in Kirkuk at the beginning of the twentieth century, the retreat of the Ottoman Empire authority, the British occupation of Iraq began, and after Sykes-Picot Agreement in 1916, the right of exploration and exploitation of oil became for the British with 25% as a share for the French, so Iraqi oil was monopolized by the Iraqi Oil Company (IPC), under the concession agreement granted since 1928. The British and French monopoly companies exploited oil and extracted in large quantities and randomly to increase profits with a small share for the country which owns the resources. This resulted in the issue of Act No.80 for 1961 in the Republican era, which enabled Iraq to recover 99% of the land that was under the control of foreign companies. The National Oil Company was established under Act. No. 11 for 1964, and in the 1970s the operations of Iraq Oil Company Limited were nationalized, giving the National Oil Company the opportunity to explore, exploit and produce oil. In fact, nationalization constituted a significant qualitative leap in terms of increasing oil revenues, in addition to the prosperity and development, especially after the rise of oil prices in the seventies. But after 1980 and the entry of Iraq in fruitless wars, reflected on the nationalization achievements; production of oil declined significantly, especially after 1990 and the invasion of Kuwait till the occupation of Iraq in 2003, which led to the looting of oil fields and the destruction of some of them, therefore the oil sector was in a serious situation, prompting the operators in this sector in 2009 to resort to rounds of licenses to reinvest investment and production in this sector, in fact this option is a justification for the advancement of the Iraqi oil sector at present, but it is no longer the best option to promote it.